(untitled) (Research, Society and Development, 2020)
Obesity is the excessive accumulation of body fat, which causes damage to the health of individuals, such as breathing difficulties, dermatological problems and disorders of the locomotor system and favors the emergence of potentially lethal chronic non-communicable diseases. There are several strategies and tools available to the professional nutritionist to carry out the treatment of overweight and obesity, among them, intermittent fasting, which is a diet protocol that aims to alternate periods of food intake and fasting. The goal is to make the body use the fat stores and with that there is a loss of fat mass, the periods when feeding is allowed are called feeding windows. The study is an integrative review of the literature in Nutrition, with the objective of reviewing the studies that evaluated the applicability of the intermittent fasting protocol in the treatment of overweight and obesity in adult individuals, with emphasis on the aspects of weight loss and improvement of biological markers of health. 10 scientific articles with the highest number of production in the year 2018 were researched and examined. The analyzed articles pointed out that Intermittent Energy Restriction (IER) is an effective dietary alternative to promote weight loss in overweight / obese adults in the short term thus, it can be used in the treatment in a safe way. The results show that IER can result in weight loss in adults with overweight and obesity comparable to traditional Daily Energy Restriction (DER).